ANTENATAL CARE UTILISATION AND SERVICES RECEIVED BY PREGNANT WOMEN IN PANMADINA RURAL COMMUNITY IN NORTH-WESTERN NIGERIA - SAMBO MN; IDRIS SH; ABDULLAHI AU; ONYEMOCHO OA (Ntec Specialist, 2009)
Background: Antenatal care is one of the important keys in ensuring safe pregnancy and childbirth. The pattern of utilization of antenatal services however varies in different regions of the country as a result of certain factors such as socioeconomic and socio-cultural factors on the part of the consumers, and quality of service on the part of the providers. Objectives: To determine the pattern of utilization of antenatal care services and the services received by women in Panmadina rural community in north western Nigeria. Method: A cross sectional study that employed systematic random sampling method to interview 280 women of reproductive age group using structured interviewer administered questionnaire. The data collected was cleaned and validated and analyzed using SPSS version 15.0. Results: A total of 280 questionnaire out of the 300 administered were completely returned giving a response rate of 93.5 %. As shown in table 1 the mean age of the respondents was 26.8+8years. Almost all (98.6) were married; majority (83.2%) had only Qur'anic education. About one-quarter (26.1%) of the respondents were full time house wives. Almost two-third (61.8%) of the respondents married at the age of 10 to 14 and more than two-quarter (65.4%) of those that had been pregnant had their first pregnancies between the ages 15 to 19. With respect to parity level half (50.0%) had children between 1 and 4, more than a quarter (27.5%) had more than 8 children while less than a quarter (22.5%) had between 5 and 7 children. Less than two-third (59.3%) of the respondents attended ANC, of this figure more than four-fifth attended ANC in the primary health centre. Cultural factors accounted to almost half (45.5%) of why some do not attend ANC. The ANC services received revealed that more than 90% of the respondents received haematenics, weighing, blood pressure check and abdominal examinations, these are followed by Urine tests, tetanus Toxoid vaccination and blood tests the which accounted for more 80% each. Furthermore, more than, three-quarters (75.4%) had height measurement, while ITN provision and HIV screening accounted for the least services received accounting for 34.1% and 21.6% respectively. Conclusion: The result of the study shows that the rate of utilization of ANC services in this community is still low. The low utilization rate was significantly contributed to the cultural factors among other things. As to the ANC services received wide gaps exist in the area of ITN distribution and HIV screening. There is therefore the need to intensify health awareness campaign on ANC utilization through effective information, education and communication strategy. Furthermore, there is the need for proper integration of Roll Back Malaria and Prevention of Maternal and Child Transmission of HIV infections services in the ANC services at primary care level.